Psychopathic Traits and Ability Emotional Intelligence in Incarcerated Males. - Gómez-Leal, Raquel; Megías-Robles, Alberto; Sánchez López, María Teresa; Fernández-Berrocal, Pablo (Colegio Oficial de la Psicología de Madrid, 2021)
Recent years have seen a growing interest in studying the factors that could help reduce the negative consequences of psychopathic traits, such as violence or criminal acts, given the effect these have on our society. This study aims to investigate the relationship between ability emotional intelligence (EI) and psychopathic traits in a sample of incarcerated men. In total, 63 incarcerated adult males (Mage = 37.51) completed the Mayer-Salovey-Caruso Emotional Intelligence Test (MSCEIT) and the 34-item Self-Report Psychopathy Scale-III (SRP-III). Comparisons using t-tests revealed that our sample showed significantly higher psychopathic traits and lower ability EI in comparison with nonincarcerated samples. Correlation analysis revealed a negative relationship between EI total score and the callous affect sub-dimension of psychopathy. Moreover, mediation analyses supported the existence of an indirect effect of EI total score on the psychopathy sub-dimensions of erratic lifestyle, criminal tendencies and interpersonal manipulation through the mediation effect of callous affect. These findings could help to inform the design of prevention and intervention programs implemented in penitentiary centers, which could have important implications for reducing antisocial and disruptive behaviours and improving possible future reintegration into society.
CC BY-NC-ND
Keywords: Psicopatología; Madurez afectiva; Emociones - Gestión; Hombres presos; Emotional intelligence; Psychopathy; Incarcerated population; MSCEIT; Mediation analysis